Using a grounded theory approach to understand the process of teaching soft skills on the job so to apply it in the hospitality classroom. (June 2020) - Crawford, Alleah; Weber, Melvin R.; Lee, JungHoon
Abstract: In the competency research related to management, essential competencies include skills that can be classified as soft skills. This research seeks to better understand how soft skills are taught by managers on the job and to provide faculty with an understanding of this process so that faculty can replicate the efforts of managers. In order to achieve this purpose, the researchers employed grounded theory, utilizing Weber et al.'s (2013) five factor model of soft skills a theoretical framework. A grounded theory of how managers teach soft skills on the job is developed and practical implications are discussed.